Factors Affecting Company Financial Performance Using Human Resource Accounting as an Intervening Variable Empirical Study on Service Companies Listed on the Stock Exchange of Thailand (SET) - Diana Dwi Astuti; Lia Rachmawati (Institut Teknologi dan Bisnis Widya Gama Lumajang, 2022)
This study aims to analyze the factors that affect the company's financial performance with human resource accounting as an intervening variable in service companies listed on the Stock Exchange Of Thailand (SET). The population in this study were all companies listed on the Stock Exchange Of Thailand (SET). This research method uses classical assumption test which includes normality test and multicollinearity test, path analysis and hypothesis testing with partial test (t test). Classical assumption test consisting of normality test and multicollinearity test. The results showed that Human Resource Accounting Disclosures did not have a relationship between the variables of Company Size, Product Diversification, Company Age, Ownership Concentration and Type of Industry on Financial Performance. Disclosure of Human Resources Accounting does not mediate between the variables of Company Size, Product Diversification, Company Age, Ownership Concentration and Type of Industry on Financial Performance.